English Summaries - Exe Christoffersen, Erik (Peripeti, 2022)
Hostages of Me by Tue Biering and Hvad har vi egentlig haft gang i? Etiske, sociale og kunstneriske undersøgelser by Jeppe Kristensen: In two articles, the founders of FIX&FOXY are reflecting on how the production company can develop theater and performances, in order to make the audience reflect on societal dilemmas. Interviews Pretty Woman Walking Down the Street. Interview with Biering and Kristensen by Gade. The interview explores the artistic strategy around the performance Pretty Woman A/S (2008), performed by female prostitutes, which triggered a strong public debate. Møder, relationer, populærkultur og repræsentation. Interview with Bering by Gade. In this conversation, Gade draws a portrait of FIX&FOXY’s practices, and identifies some fundamental themes in contemporary theatre. Udflugt til ungdomsland. Interview with Kristensen by Christoffersen and Krøgholt. Kristensen reflects on the process of Youth (Ungdom) focusing and on how the company created ownership for the young participants, to give agency as co-developers of the performance’s various spaces. My Deer Hunter. Interview af de medvirkende og det kreative team. Interview with participants from My Deer Hunter by Christoffersen, Krøgholt og Winkelhorn. In dialouge with four participating veterans and the artistic team behind My Deer Hunter, the interview explores, how the performance and rehearsal process functioned for a group of PTSD affected veterans, and how their histories and participation in war was challenged. FIX&FOXY’s poetik, metode og organisering. Interview with Biering by Christoffersen, Krøgholt and Winkelhorn. Biering tells about the principles and the theatre view that have been guiding for FIX&FOXY’s creative and theatrical strategies throughout the theatre’s work. Articles Europæerne. En postdramatisk tilgang til klassikerne by Mads Thygesen. How did the staging of The Europeans exploit classics as a tool to intervene and mix in a current historical and political context? The common denominator for the work was European wars as a dramatic focal point. The article discusses how this performance illuminates the seed of FIX&FOXY’s poetics and conceptual thinking from 2005. Mod alle Odds. Tragedie og statistik by Erik Exe Christoffersen. Against All Odds (2019) are based on identity, representation, and statistics, which portrays how today’s young persons’ lives would statistically look in the future. The question raised by Christoffersen is, how the dramaturgy of the performance creates communication. Forvaltningen af publikums ubehag. FIX&FOXY som politisk konfrontationskunst by Laura Luise Schultz. She describes the approach to the audience in various of performances and highlights, that a central feature of FIX&FOXY’s political remediation is their sophisticated engagement with the audience and managing of the audience’s discomfort. Love Theater. Uhåndgribelige konflikter by Jeppe Kristensen. Kristensen went to Bangkok to cast a prostitute who should play the leading character in Love Theater. The performance was based on her own life-experiences as prostitute, and the article is reflecting on intangible conflicts, regarding the prejudices of an audience. Samtidskunst, repræsentation og remediering by Erik Exe Christoffersen. Christoffersen emphasizes FIX&FOXY’s way of doing remediation, perceived as a way of ‘overpainting’ a work like a palimpsest. Verdensteater og øjebliksteater by Jeppe Kristensen. Kristensen gives an overall artistic discussion of FIX&FOXY and draws a thread from the company’s beginning as a theatrical variant of contemporary art, to Peter Osborne’s analysis of what contemporary art is today. Essays FIX&FOXYs distribuering af ledelse by Ida Krøgholt. Krøgholt is unfolding FIX&FOXY’s way of working as distributed facilitation, where the participants facilitate each other, and thus through the theatre process develop an awareness of communication and observation. FIX&FOXY’s representation strategies by Anne Liisberg. Liisberg raises the important questions: Who and how can we represent? And who will never be represented?